E-learning prospect on improving academic performance in Omani Universities - Tawafak, Ragad M.; Awanis, Romli; Ruzaini, Abdullah Arshah (IOP Publishing Ltd., 2019)
This paper will discuss the impact of E-Learning prospect on the improvement of learner academic performance of Oman universities. The study explains the needs to expand working on E-Learning models and continue use of face to face traditional educational process. The real problem faced education is a need for several applications and technologies to improve their outputs and improve on teacher-student prospect. This paper aims to present an expanded review of different E-learning models to evaluate the prospect of their academic performance. The method of this paper divided into two phases. In the first phase, including the analysis of different technologies and most used tools affected in the educational process to measure the acceptance of learning outcomes. The Second phase, show the testing and validation of learner prospect of E-Learning to enhance the learning process and improve the academic performance.